Chemical pavement modifications to reduce ice adhesion - Wright, Michael; Parry, Tony; Airey, Gordon (Institution of Civil Engineers, 2016)
The formation of ice and snow on road pavement surfaces is a recurring problem, creating hazardous driving conditions, restricting public mobility as well as having adverse economic effects. It would be desirable to develop new and improved ways of modifying the pavement surface, to prevent or at least delay the build-up of ice and to weaken the pavement–ice bond, and making the ice which forms easier to remove. This development could lead to economic, environmental and safety benefits for winter service providers and road users. This paper describes how environmental scanning electron microscopy was used to examine the mechanism by which de-icing chemicals, added as a filler replacement to bituminous materials, can be transferred to the pavement surface. The paper assesses the potential for chemical modifications to reduce the adhesion between ice and the pavement surface by means of work of adhesion calculations, based on surface energy parameters and a new physical ice bond test. The paper also examines the influence that the chemical modifications have on the durability of the pavement surface course.